PTU-052 The natural history of low-grade dysplasia in patients with barrett's oesophagus: a tertiary centre experience. (June 2019) - Hussein, Mohamed; Seghal, Vinay; Magee, Cormac; Sami, Sarmed; Banks, Matthew; Sweis, Rami; Graham, David; Morris, Danielle; Rodriguez, Manuel; Jansen, Marnix; Novelli, Marco; Lovat, Laurence; et al.
Abstract : Introduction: Barrett's Oesophagus (BE) is associated with increased risk of oesophageal cancer (EAC). The optimal management of low-grade dysplasia (LGD) arising in BE remains controversial. We performed a retrospective study from a tertiary referral centre for BE neoplasia, to estimate time to progression in patients with confirmed LGD compared to down-staged LGD. Methods: We carried out retrospective analysis of tertiary BE LGD referrals in a single tertiary centre (July '06-October '18). Patients underwent high definition white light endoscopy with chromoendoscopy with targeted and Seattle protocol biopsies following referral. All biopsies were reviewed by at least two expert pathologists. We carried out analysis in ablation naïve patients with at least one follow-up endoscopy post index procedure. The primary end point was time to progression to high grade dysplasia (HGD)/EAC. Results: 141 LGD patients were included. 13 were diagnosed during surveillance at our centre. 128 were tertiary referrals. 43/128(34%) were upstaged at index endoscopy after referral to HGD/intramucosal adenocarcinoma (IMC). 44/128(34%) were down-staged, 28/128(22%) to non-dysplastic Barrett's oesophagus (NDBO), 15/128(12%) to indefinite for dysplasia (IND), one had no BE on index endoscopy. In the NDBO/IND group, 34 had no ablations and at least one follow-up endoscopy, 5/34(15%) progressed to HGD/IMC over a median time of 36 months (IQR, 13-42). 41/128(32%) of all referrals had confirmed LGD at index endoscopy. There was 54/141(38%) confirmed "true" LGD including patients diagnosed under our surveillance programme. In this cohort 34 had no ablations and at least one follow-up endoscopy. 10/34(29%) progressed to HGD/IMC over a median time of 10 months (IQR, 4-16). The remainder of this cohort had a median follow up of 27 months (IQR, 14-45), and average number of 2 follow-up endoscopies with biopsies. Analysis of RFA naïve patients (table 1 ). Conclusion: Our data shows the variability in the diagnosis of LGD from referring centres, with 32% of referrals with confirmed LGD. The cumulative incidence of progression to HGD/IMC and time to progression varied across subgroups. Confirmed LGD had a shorter progression time compared to the down-staged group (NDBO/IND). It is important to differentiate these subgroups so that decisions on surveillance/endotherapy can be more personalised and resources utilised more wisely.